Tantangan dan Peluang Perkembangan Teknologi Pertahanan Global Bagi Pembangunan Kekuatan Pertahanan Indonesia - Angga Nurdin Rachmat (Jurnal Transformasi Global, 2014)
Abstract The application of technology has been developing throughthe history of many nations’ defence system.Nations always make their effort to increase research on defence technology system as it strengthens their defence capability to address the threat resulted from the development of defence technology system. Indonesia must have catch-up strategy to acquire the updated defence technology system. This paper is to discuss the global defence technology that bring obstaclesas well as chances toward Indonesia defence system, especially those related to development and adaptation capability from Indonesia’s defence industries.                        Keywords : Defence industries, Indonesia, military technology, TNI